Analysis of The Influence of Pentagon Fraud in Detecting Financial Statement Fraud Using Method F- Score - Vina Yusniarti; Henny Mulyati; Amrizal Amrizal (Procedia of Social Sciences and Humanities, 2021)
This study aims to examine the elements of fraud in the fraud pentagon theory in detecting financial statement fraud. Pentagon fraud is variables from the pressure element, opportunity, rationalization, capability, and elements of arrogance, namely political relationships which are hypothesized to affect financial statement fraud. The F-Score method is used to determine financial statement fraud. This research sample was selected using the purposive sampling method from 47 manufacturing companies in the basic industry and chemicals industry listed on the Indonesia Stock Exchange (BEI) in the period 2015 to 2019. Hypothesis testing uses multiple regression analysis models using SPSS 22 to test the effect of the target. finance, financial stability, external pressure, institutional share ownership, ineffective supervision, influence on the nature of the industry, quality of external auditors, replacement of auditors, change of directors and political relations to financial statement fraud. The results showed that the quality of external auditors and auditor turnover had a significant positive effect on financial statement fraud. Meanwhile, financial targets, financial stability, external pressure, institutional share ownership, ineffective supervision, the influence of the nature of the industry, the change of directors, and political relations have no effect on financial statement fraud.